Run the Race - Hofer, Evan; Reinhardt, Kelsey; Williamson, Mykelti; Fisher, Frances; 1952-; 1977-; Van Peebles, Mario; Polaha, Kristoffer; 1995; Dowling, Chris; Moorman, Darren; McEntire, Jake; et al. (University City, CA, 2019)
Reeling from his mothers death and his fathers abandonment, Zach, an All-State athlete, finds glory on the football field, working to earn a college scholarship and the brothers ticket out of town. When a devastating injury puts Zach and his dreams on the sidelines, David laces up his track cleats to salvage their future and point Zach toward hope.
Keywords: Brothers; Drama; Accidents; Drama; Mothers; Death; Drama; Video recordings for the hearing impaired; Sports films; Fiction films; Feature films